2011
DOI: 10.1007/s13369-010-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Earthquake Characteristics on Seismic Performance of RC Elevated Water Tanks Considering Fluid Level within the Vessels

Abstract: The dynamic behavior of a liquid storage tank as a special structure differs from that of general structures. Important structures of cylindrical shape are used to store vital products, such as water and petroleum products, for cities and industrial facilities. Damage to these structures during a strong ground motion may lead to fire or other hazardous events. Liquid storage tanks are lifeline structures and strategically very important, since they have vital use in industries and nuclear power plants. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Cheng et al [1][2][3] theoretically studied the liquid-soil interaction (LSI) vibration characteristics and seismic response of rectangular liquid storage. Shakib and Omidinasab [4] studied the seismic behaviors of elevated concrete water towers under different liquid heights and different seismic loads. Livaoglu [5] studies showed that the soil-structure interaction and the structural properties of supporting system for the elevated tanks affected the sloshing response of the fluid inside the vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [1][2][3] theoretically studied the liquid-soil interaction (LSI) vibration characteristics and seismic response of rectangular liquid storage. Shakib and Omidinasab [4] studied the seismic behaviors of elevated concrete water towers under different liquid heights and different seismic loads. Livaoglu [5] studies showed that the soil-structure interaction and the structural properties of supporting system for the elevated tanks affected the sloshing response of the fluid inside the vessel.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic vulnerability of water supply systems has been widely studied so far [3][4][5][6][7][8][9]. Likewise, the seismic performance of overhead water tanks built with and without seismic code provisions has been reported in the literature (see, for example, [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Their study analyzed the tank under various earthquake records (and thus different frequency contents) and concluded that frequency content affects the structure responses. Shakib and Omidinasab [16] studied the response of an elevated water storage tank under ground motions with different frequency contents. They found out that earthquakes with low-frequency contents affect the first convective mode more severely and result in large vertical displacements on the free surface of the water.…”
Section: Introductionmentioning
confidence: 99%